Maimonides the Rationalist. - Davidson, Herbert A. (Littman library of Jewish civilization (Series), 2011)
Maimonides was not the first rabbinic scholar to take an interest in philosophy, but he was unique in being a towering figure in both areas. His law code, the Mishneh torah, stands with Rashi's commentary on the Babylonian Talmud as one of the two most intensely studied works of medieval rabbinic scholarship, while his Guide for the Perplexed is the most influential and widely read Jewish philosophical work ever written. Admirers and critics have arrived at wildly divergent perceptions of the man. We have Maimonides the atheist or agnostic, Maimonides the skeptic, Maimonides the deist, Maimoni.